Bidirectional power flow in an electric vehicle using predictive control algorithm including sneak circuit analysis - Eti, Sri Latha; Sudha, Kasibhatla Rama; Lahari, Molleti Venkata Pankaj; Sekhar, Akkapeddi Chandra (Institute of Advanced Engineering and Science, 2024)
The use of electric vehicle battery chargers is becoming more common for transferring power between grid and energy storage system. This paper focuses on providing a comprehensive understanding of various modes of operation of these battery chargers. Two different controllers are used; one is the predictive power controller at the grid end to generate active and reactive power references to operate a 3-phase AC/DC converter connected between the power grid and the DC link and the other is a hysteresis current controller used to operate a reversible DC/DC converter connected between the DC link and electric vehicle battery and is considered as the main component of the energy storage system. Also, sneak circuit analysis is carried out on the DC/DC converter and the controller is designed accordingly. Results from simulations validate the suggested control scheme's viability and efficacy. The adopted topology is validated in real time with dSpace 1104 hardware in the loop prototype operating in different scenarios, both in steady-state and during transients.